Graphene homojunction: closed-edge bilayer graphene by pseudospin interaction. Issue 17 (26th January 2016) - Yan, Jiaxu; Li, Chao; Zhan, Da; Liu, Lei; Shen, Dezhen; Kuo, Jer-Lai; Chen, Shoushun; Shen, Zexiang
Abstract : Depending on the sublattices they are propagated in, low-energy electrons or holes are labeled with pseudospin. Abstract : Depending on the sublattices they are propagated in, low-energy electrons or holes are labeled with pseudospin. By engineering pseudospin interactions, we propose that two critical features of a junction, i.e., band gap opening and spatial charge separation, can be realized in graphene layers with proper stacking. We also demonstrate theoretically that such a graphene diode may play a role in future pseudospin electronics such as for harvesting solar energy.